Instructional design for effective classroom Pedagogy of teaching - Mallillin, Leovigildo Lito D.; Mallillin, Jocelyn B.; Ampongan, Yolanda D.; Lipayon, Imelda C.; Mejica, Mercy M.; Burabo, Jocelyn Z. (S&Co Publishing, 2023)
The study aims to examine the contribution of instructional design for effective classroom pedagogy of teaching among the respondents and identifies what makes instructional design that leads to effective classroom pedagogy of teaching among the respondents. The research employs the descriptive quantitative design because the method describes the variables and characteristics of the study. Purposive sampling is highlighted in the study. The study comprised Seventy (70) respondents only. Results show that learning process and strategy for effective pedagogy of teaching show to actively involve instruction that will lead students for better learning outcome, show to involve critical thinking, formation, analyzing inferences, and knowledge of the lesson, show to provide a phase of instructional design to effective teaching in applying, inferring, analyzing pedagogy and various learning experiences, show to advance technology of teaching to equip students with better learning, and show to rely on interactive instruction sharing and heavy discussion, role playing, peer learning, cooperative learning, simulation, and discussion. Findings show that there is a significant correlation on the contribution of instructional design for effective classroom pedagogy of teaching as observed among the respondents.